Novel Synthesis of 5-Substituted 5H-Benzo[b]carbazole-6,11-diones via Double Buchwald–Hartwig Reaction - Bolibrukh, Khrystyna; Khoumeri, Omar; Polovkovych, Svyatoslav; Novikov, Volodymyr; Terme, Thierry; Vanelle, Patrice (Synlett, 2014)
2-Bromo-3-(2-bromophenyl)naphthalene-1,4-dione was synthesized as a key precursor to obtain a number of functionalized benzo[b]carbazole-6,11-diones by double Buchwald–Hartwig coupling reaction.
Keywords: quinone; anilines; Buchwald–Hartwig reaction; carbazole; one-pot